2014
DOI: 10.1002/nau.22559
|View full text |Cite
|
Sign up to set email alerts
|

An overactive bladder symptom and health-related quality of life short-form: Validation of the OAB-q SF

Abstract: The OAB-q SF captures the full spectrum of OAB Symptom Bother and HRQL impact with good reliability, validity, and responsiveness, while being less time-consuming for patients to complete.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
296
1
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(307 citation statements)
references
References 33 publications
2
296
1
8
Order By: Relevance
“…• Moderate (symptom score range [8][9][10][11][12][13][14][15][16][17][18][19] • Severe (symptom score range 20-35)…”
Section: Ipss (International Prostate Symptoms Score)mentioning
confidence: 99%
See 1 more Smart Citation
“…• Moderate (symptom score range [8][9][10][11][12][13][14][15][16][17][18][19] • Severe (symptom score range 20-35)…”
Section: Ipss (International Prostate Symptoms Score)mentioning
confidence: 99%
“…The instrument was developed and validated in both continent and incontinent OAB patients, including both men and women [11].…”
Section: Oab-q Sfmentioning
confidence: 99%
“…changes, and concurrent medical disorder such as diabetes. 5 OAB is defined by the international continence society (ICS) as a complex of symptom characterized by urinary urgency, with or without urge incontinence, usually with frequency and nocturia in the absence of urinary tract infection or other obvious pathology. 6 Urgency is defined by The ICS as the complaint of sudden, compelling desire to pass urine which is difficult to defer.…”
Section: Introductionmentioning
confidence: 99%
“…The 2014 survey in Taiwan also revealed that 35% of Taiwanese women were aware of their OAB symptoms. OAB symptoms often negatively affect the social life, work, mood, family life, and sex life of patients and thus seriously affect their quality of life [18,19,[22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%